Controller Design Considerations for ACM APFC Systems. (30th October 2012) - Abramovitz, Alexander
Abstract : This paper is concerned with performance of the current shaping network in Average Current Mode (ACM) Active Power Factor Correction (APFC) systems. Theoretical expressions for the ripple components are derived. Then, ripple interaction and impact on the current loop reference signal are investigated. A modification of the controller network is suggested that results in an improved Total Harmonic Distortion (THD). Design guidelines are suggested. The theoretical predictions were validated by simulation.